Modelagem e avaliação de desempenho da suspensão passiva de barras de pulverização - Kappaun, Rafael (2020)
The uniformity and quality of the application of an agrodefensive depends on the stability of the spray boom, defined by the passive suspension system between the boom and the sprayer chassis. The objective of this study is to present a procedure for modeling and identifying parameters to improve the performance of passive spray boom suspensions. With the aid of dedicated software, two multi-body dynamics models of a tractor-sprayer assembly are developed to evaluate the suspension system: a rigid body dynamic model (RBD) and another finite element model (MEF) containing deformable bodies. Experimental tests are performed to calibrate the models, monitoring the accelerations of entry and response in the suspension and displacements of the damper and rubber springs. It is concluded that the MEF model is more suitable for the assessment of horizontal bar oscillations. The average RMS and the normal curve are suitable tools to identify the most stable suspension configuration. The horizontal stiffness of the boom has a great influence on oscillatory displacements and its behavior must be included in the simulation models. Resizing the bar structure can reduce horizontal oscillations.